Enfrentamentos na produção: os profissionais da criação, o campo e a construção do masculino na publicidade - Santos, Filipe Bordinhão dos (2017)
The present research is a study of advertising production from the perspective of the creative, for this we investigate how the field is constituted, mobilized and institutionalized and in what way it affects, in the last instance, the publicity creation as for the representation of the man in the announcements. However, even before the creatives entered the field as producers, we recognize these individuals with a specific subjective and social formation responsible for provoking confrontations in this social space. For this, initially, we used the Mediation Theory (MARTÍN-BARBERO, 2006) and especially the Social Fields Theory (BOURDIEU, 2008) to understand the tensions of the creative with the agents, the institutions and the economic and cultural logics that production practices. The articulation of the clash between individual and collective is made through the discussion about the process of social construction of the masculinity (s) in advertisements. Thus, to carry out the empirical study of advertising production we take advantage of the methodological precepts of the reception to immerse in the reality of creative professionals working in advertising agencies in the city of Porto Alegre/RS and Curitiba/PR. We understand that these are agents that are in a subfield (the agencies) privileged of the advertising process and where it concentrates a set of forces and "voices" that need to be placed in the materialization of the image of the man in ads. Finally, we identify how the sample of respondents, regardless of the age group and time of professional performance, is homogeneous regarding the criticism of how (still) the man is represented by advertising, mainly because of a sociability that rejects or hegemonic pattern of masculinity. In addition, although incipient, the professionals researched suggest a movement of social transformation about to the acceptance and visibility of alternative forms of masculinity, a fact that stresses the productive process of advertising and incorporates such representations in contemporary advertisements.